Novel technique to reduce prolapsed device in atrial septal defect closure - Liao, Li-Chin; Jan, Sheng-Ling; Lin, Ming-Chih; Lee, Ho-Hsun; Fu, Yun-Ching (Frontiers in Cardiovascular Medicine, 2023)
Objective Transcatheter closure of atrial septal defect (ASD) has become an alternative treatment to surgical repair. One of the challenges is the prolapse of the left atrial disc during the procedure. Many techniques have been developed to prevent the prolapse but not reduce it. In this study, we present a novel technique, termed push back technique, that help reduce the prolapsed device. Methods We enrolled 24 patients (8 males, 16 females) between May 2008 and January 2023 who underwent the push back technique during transcatheter closure of ASD in Taichung Veterans General Hospital. We recorded the hemodynamic data, success rate and complications including device embolization/migration, valvular regurgitation, pericardial effusion, and residual shunt. Results The median age was 6.3 years (1.2-70.5 years) and the median weight was 19.1 kg (7.8–90 kg). Fifteen (62.5%) patients had mild pulmonary hypertension. The median Qp/Qs was 2.54 (1.5–8.8). The median ASD stretched size was 21.2 mm (7.7–35.3 mm). The median device size was 22 mm (8–40 mm). The median fluoroscopy time was 14 min (5–23 min) and median procedure time was 47 min (25–78 min). The push back technique successfully reduced the prolapsed device in 21 (87.5%) patients. There was no complication in all patients. Conclusion We present a novel push back technique that can successfully reduce the prolapsed device in 87.5% (21/24) patients without complications. It is feasible, safe and effective.